Sustainability of Local Food Festivals: A Framework to Estimate Environmental Impacts - Sandra, Notaro; Alessandro, Paletto (Journal of Environmental Accounting and Management, 2026)
Environmental sustainability is aimed to improve human welfare and well-being by maintaining the integrity of the life supporting systems of the Earth. The aim of this study is to propose a framework to quantify and analyze the environmental impacts generated by local events and festivals. The proposed framework was tested in a local food festival in Italy and structured in two steps: collection of primary data; processing them based on the principles of Life Cycle Assessment (LCA) approach. The results show that the 5,210 visitors that attended the three days of the food festival produced a total of 0.043 kg of waste per capita and 16 kg CO_2eq. per capita. The total environmental impacts caused by all the participants in the three days were: climate change (83,270 kg CO_2eq.), particulate matter formation (162 kg PM10_eq.), photochemical oxidant formation (530 kg NMVOC), terrestrial acidification (439 kg SO_2eq.), and freshwater eutrophication (9.17 kg P_eq.). The results show that the highest environmental impacts are due to the transport of exhibitor members and materials, while visitor transport has a low impact considering that 80% are local visitors who went to the event on foot or by bike. This study provides indications to the organizers to reduce the environmental impacts in future editions and data to policy makers for defining hectares of reforestation needed to compensate the CO_2eq. emissions of the event.